2008
DOI: 10.1103/physrevlett.100.192302
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of theω-Meson Lifetime in Nuclear Matter

Abstract: Information on hadron properties in the nuclear medium has been derived from the photoproduction of omega mesons on the nuclei C, Ca, Nb, and Pb using the Crystal Barrel/TAPS detector at the ELSA tagged photon facility in Bonn. The dependence of the omega-meson cross section on the nuclear mass number has been compared with three different types of models: a Glauber analysis, a Boltzmann-Uehling-Uhlenbeck analysis of the Giessen theory group, and a calculation by the Valencia theory group. In all three cases, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 30 publications
1
33
1
4
Order By: Relevance
“…This quantity was previously measured in nuclear photoproduction of ω and φ mesons [28][29][30], from which large in-medium widths of ∼100-150 MeV were extracted (see also Refs. [26,31,32] for theoretical evaluations).…”
Section: Transparency Ratio (Yield)mentioning
confidence: 98%
“…This quantity was previously measured in nuclear photoproduction of ω and φ mesons [28][29][30], from which large in-medium widths of ∼100-150 MeV were extracted (see also Refs. [26,31,32] for theoretical evaluations).…”
Section: Transparency Ratio (Yield)mentioning
confidence: 98%
“…We illustrate two different results: the first includes all ω productions (red squares) while the second takes only into account the primary ω production (black circles). We compare them to experimental data [77] and with calculations according two different models, namely, the Boltzmann-Uehling-Uhlenbeck transport code calculation by the Geissen group [77] and a Monte Carlo analysis by the Valencia group [77]. Experimental data were obtained in the Crystal Barrel/TAPS detector at the ELSA tagged photon facility in Bonn [77].…”
Section: E Nuclear Transparency For the ω Mesonmentioning
confidence: 99%
“…In Refs. [30] and [80] the transparency ratio was used to determine the width of the ω meson in finite nuclei using a BUU transport approach. U.…”
Section: Nuclear Transparency In Thementioning
confidence: 99%
“…In fact, a recent reanalysis of the background of the reaction concluded that one cannot * tolos@kvi.nl determine the shift of the ω mass in the nucleus from that reaction [28]. In contrast, determination of the ω width in the medium by means of the production cross section in different nuclei, which leads to the transparency ratio [29], was rather successful, giving rise to an appreciable in-medium enhancement [25,30].…”
Section: Introductionmentioning
confidence: 99%